The phenome analysis of mutant alleles in Leucine-Rich Repeat Receptor-Like Kinase genes in rice reveals new potential targets for stress tolerant cereals - Dievart, Anne (Plant science : an international journal of experimental plant biology, 2016)
Copyright © 2015 The Authors. Published by Elsevier Ireland Ltd.. All rights reserved.